Pelleting and Starch Characteristics of Diets Containing High Amylase Corn - C. N. Truelock; M. D. Tokach; C. R. Stark; C. R. Paulk (Kansas Agricultural Experiment Station Research Reports, 2019)
This experiment was designed to evaluate the effects of die thickness and conditioning temperature on pelleting and starch characteristics in diets containing either conventional yellow dent or high amylase corn (Enogen®, Syngenta Seeds, LLC). Treatments were arranged as a 2 × 2 × 3 factorial of corn type (conventional and high amylase), die thickness (L:D 5.6 and 8.0), and conditioning temperature (165, 175, and 185°F). For the high amylase corn treatments, ground high amylase corn replaced conventional ground corn on a lb:lb basis. Diets were pelleted via steam conditioning (10 in × 55 in Wenger twin staff pre-conditioner, Model 150) and using a pellet mill (CPM Model 1012-2) with a 5/32 in × 7/8 in (L:D 5.6) or 5/32 in × 1 1/4 in (L:D 8.0) pellet die. Conditioner retention time was set at 30 sec and production rate was set at 33 lb/min. All treatments were replicated on 3 separate days. Pellets were composited and analyzed for starch and pellet durability index (PDI). Conditioning temperature, hot pellet temperature (HPT), production rate, and pellet mill energy consumption were recorded throughout each processing run. Data were analyzed using the GLIMMIX procedure in SAS (v. 9.4, SAS Institute Inc., Cary, NC), with pelleting run as the experimental unit and day as the blocking factor. The 3-way interaction was not significant (P>0.15) for any of the pelleting or starch responses analyzed in this study. There was no evidence (P>0.14) for a corn type × conditioning temperature interaction for HPT, PDI, or energy consumption. There was a tendency (P= 0.08) for a corn type × die thickness interaction for PDI. The PDI for the high amylase and conventional corn treatments were similar when diets were pelleted using the L:D 8.0 die. However, PDI for conventional corn diets was greater than high amylase corn diets when pelleted using the L:D 5.6 die. Pelleting diets with the L:D 8.0 die had improved (P<0.01) PDI compared to the L:D 5.6. Additionally, PDI increased (linear,P= 0.03) with increasing conditioning temperature. Pellet mill energy consumption was greater for the thicker pellet die (P= 0.02), and tended to decrease (quadratic,P= 0.07) with increasing conditioning temperature. There was a corn type × conditioning temperature interaction (P= 0.01) for gelatinized starch in conditioned mash. High amylase corn diets steam conditioned at 185°F had greater gelatinized starch than all other corn type × conditioning temperature treatments. Cooked starch of conditioned mash was greater for diets containing high amylase corn compared to conventional corn and increased (linear,P<0.01) with increasing conditioning temperature. There was a corn type × die thickness interaction (P<0.01) for total starch in pellets. Total starch was greater for high amylase corn diets pelleted using the L:D 8.0 compared to the L:D 5.6 die, but not different from the conventional corn diets pelleted using either the L:D 5.6 or 8.0 die. Starch gelatinization was greatest (P<0.01) for the high amylase diets and increased (linear,P= 0.05) with increasing conditioning temperature. Lastly, pelleted high amylase corn diets had a greater percentage (P<0.01) of cooked starch compared to conventional corn diets, and there was a tendency (P= 0.06) for cooked starch to increase with increasing conditioning temperature. In conclusion, increasing die L:D and conditioning temperature improved pellet quality. Starch gelatinization was increased when diets were pelleted at the highest conditioning temperature of 185°F, and high amylase corn diets resulted in greater gelatinized starch than conventional corn diets.
Keywords: amylose; corn; pelleting; pigs